Peningkatan Kemampuan Berpikir Kreatif Matematis : Dampak Flipped Classroom Berbantuan Audio Visual Dan Gaya Belajar - Suliawati, Pita; Fakhri, Jamal; Sugiharta, Iip (Yayasan Darussalam Bengkulu, 2020)
The purpose of this study is to analyze to find out the influence of Flipped Classroom learning ad learning style on mathematical thinking skills. As well as To know the insteraksi between flipped classroom users with visual, auditorial, and kinesthetic learning styles towards mathematical thinking ability. The type of research used by researchers is Quasi Experiment Design. Sampling techniques used cluster random sampling technique which is a sampling strategy that is done randomly seebagai representative of the population. Data collection techniques include tests (essays) to measure students' mathematical creative thinking ability, interviews, questionnaires for auditorial, visual and kinestic information data And homogeneity test is Bartlet test, and hypothesis test using R program with post-anava test two roads is Scheffe test. The results of that analysis: There is an influence of Flipped Classroom on mathematical creative thinking skills and there is no influence of student learning styles on mathematical creative thinking skills. And there is no intraction between the treatment of learning and the category of learning styles.